WORK CULTURE, MOTIVATION, AND CAREER PROGRESSION IN ISLAMIC INSTITUTIONS: A STUDY ON ENHANCING EMPLOYEE PRODUCTIVITY - Abdul Kadir Siregar; M. Ali Musri; Epi Supriyani Siregar (Journal Analytica Islamica, 2025)
This study investigates the influence of work culture, work motivation, and career progression on employee productivity within Islamic institutions. Grounded in the theoretical integration of Organizational Culture Theory, Self-Determination Theory, and Human Capital Theory, the research acknowledges the role of Islamic Work Ethic values-such as amanah, ikhlas, and itqan-as shaping mechanisms in professional behavior. A quantitative explanatory design was employed, involving a survey distributed to employees across selected Islamic institutions in Indonesia. Simple random sampling was used to determine respondents, and data were analyzed through multiple linear regression with validity and reliability tests performed to ensure measurement accuracy. The findings demonstrate that all three independent variables significantly and positively affect employee productivity. Work culture emerged as a key determinant, emphasizing the role of shared values, teamwork, and disciplinary practices grounded in Islamic ethos. Work motivation also showed a strong effect, indicating that employees are driven not only by extrinsic incentives but also by intrinsic and spiritual motives rooted in religious consciousness. Career progression further contributed significantly to productivity, suggesting that structured development pathways and perceived fairness in advancement enhance performance in Islamic institutional settings. Overall, the results reinforce the view that value-based organizational systems integrating ethical and spiritual dimensions can enhance workforce excellence. This research contributes theoretically by contextualizing Western organizational behavior models within an Islamic moral framework and practically by offering insights for strengthening human resource strategies in Islamic institutions.